An approach for upgrading behavior and bio-oil production using CO2-assisted cellulose pyrolysis in cobalt-based Ce/Fe/Mg composite catalyst. (15th July 2023) - Liu, Haipeng; Jiang, Haifeng; Song, Jiaxing; Zhang, Ling; Zhang, Yu; Li, Yuhang; Hong, Wenpeng
Highlights: Catalysts that can effectively promote cellulose decomposition are synthesized. CO2 -assisted cobalt-based Ce/Fe/Mg catalyst enhances furans and ketones. The synthesized catalyst has good oxygen transfer ability. The performance of catalyst in improving the selectivity of compound is given. Abstract: The production of high value-added liquid products by catalytic pyrolysis of cellulose has become an effective way to realize the efficient utilization of biomass. This work synthesized a series of Co-Ce, Co-Fe and Co-Mg composite metal catalysts and used them to obtain furans and ketones production. In addition, the CO2 was used as a pyrolysis atmosphere to investigate the synergistic effect between CO2 and the prepared catalyst. The results showed that the catalyst effectively promoted the depolymerization of cellulose and improved the oxygen transfer behavior between volatile matters during cellulose pyrolysis. As a reaction medium, CO2 influenced the carbon distribution of products, thereby increasing syngas yield, and the CO2 atmosphere promoted the formation of furans and ketones. Compared with those obtained by the non-catalytic pyrolysis in N2 atmosphere, the relative contents of furans and ketones in the liquid products produced by the catalytic pyrolysis of cellulose in CO2 atmosphere increased by about 13.38% and 9.8%. In the CO2 environment, the generation ability for furans was Co-Mg catalyst > Co-Ce catalyst > Co-Fe catalyst, and the generation ability for ketones was Co-Ce catalyst > Co-Mg catalyst > Co-Fe catalyst. These works provide an important way for the efficient preparation of furans and ketones from biomass pyrolysis.